(untitled) (American Journal of Islam and Society, 2013)
This insightful book, useful to scholars and students of Islamic and South Asian history, illuminates the place of Islamic thought and institutions in the political regimes of the Delhi Sultanate (1206-1526). Finding late approaches to the historiography of the period unduly focused on “fact” and “fiction,” rather than “meaning,” the author unravels the more complex relationship between history and historiography in six pertinent chapters (p. xix). These are complemented by maps, illustrations, thorough endnotes, and a useful bibliography. As a whole, the cohort of Persian histories read lead to the convincing conclusion that “historians played a major role in producing and sustaining ideas about power, justice and Islamic rule of the premodern empire” (p. 160) ...